KINERJA PEGAWAI DALAM PELAYANAN PUBLIK PADA DINAS PENDAPATAN DAERAH KABUPATEN BARITO TIMUR - Irawanto Irawanto (AS-SIYASAH: Jurnal Ilmu Sosial Dan Ilmu Politik, 2017)
The aims of this research are: 1) To know the performance of employees in public service at Regional Revenue Service of East Barito Regency, 2) To know the obstacles in public service at Regional Revenue Service of East Barito Regency, and 3) to know solution to overcome obstacle in public service in the District Revenue Office of East Barito Regency.This research is a qualitative research. The key informant in this research is Head of Regional Revenue Service of East Barito Regency. Data were collected through interviews, observation and documentation.The results showed that: 1) Performance of employees of Revenue Service Office of East Barito Regency seen from performance indicators such as quality, effectiveness and work commitment is good but the quantity of work, the timeliness of task implementation, independence in dealing with work problems on PBB-P2 and BPHTB still not implemented optimally. 2) Obstacles faced in Public Service in the District Revenue Office of East Barito Regency, namely: a) Employee Performance not yet optimal, b) Lack of Employee Competency and Socialization, and c) Lack of Room Facilities Waiting, and 3) Solutions Can Do To Overcoming Obstacles in Public Service in the District Revenue Office of East Barito Regency, namely: a) Employee Development and Evaluation b) Technical Guidance (Bimtek) and Socialization, and c) The addition of waiting room facilities.